2013
DOI: 10.1177/0021998313503026
|View full text |Cite
|
Sign up to set email alerts
|

The influence of carbon fabric weave on the in-plane shear mechanical performance of epoxy fiber-reinforced laminates

Abstract: Woven fabrics used in composite materials are designed to fulfill specific manufacturing or structural requirements. Knowledge of the influence of the weave structure on the mechanical properties of the composite is essential to properly optimize the design of structural components. The focus of this work is to investigate the influence of the type of weave used for fabric reinforcement in polymers particularly on the in-plane shear mechanical performance. The selected materials are carbon fibers and epoxy res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Medina et al. 20 have experimentally investigated damage evolution during in-plane shear tests as a function of the composite architecture, including unidirectional laminates. The cyclic shear tests showed that the shear modulus reduces as much as 50% as plastic strain increases.…”
Section: Introductionmentioning
confidence: 99%
“…Medina et al. 20 have experimentally investigated damage evolution during in-plane shear tests as a function of the composite architecture, including unidirectional laminates. The cyclic shear tests showed that the shear modulus reduces as much as 50% as plastic strain increases.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the choice of shear test method has an impact on the results. The Composite Materials Handbook MIL-HDBK-17-1F [23] notes that the V-notched rail shear test (ASTM D7078) is the most accurate for determining shear modulus but acceptable predictions can also be made with the ±45º tensile shear test, used for much of the data in Figure 2 and Figure 3, including all those from NIAR. However, the ±45º tensile shear test does not create a pure stress state.…”
Section: Ud Specimensmentioning
confidence: 99%
“…However, the ±45º tensile shear test does not create a pure stress state. Therefore the shear modulus extracted from test data is an effective shear modulus rather than an absolute one [23].…”
Section: Ud Specimensmentioning
confidence: 99%
“…28 It was shown that the woven fabric patterns have limited effect on the composite shear performance which was carried out by a two rail shear. 29 The filament interfacial properties were modified by surface treatment and about twofold enhancement on its intra-layer and inter-layer shear strength was obtained. 30 Deng and Ye found that the fiber-matrix adhesion by fiber surface treatment and sizing improved the fracture toughness as well as the inter-layer and the intra-layer shear strength of the graphite/epoxy composites.…”
Section: Introductionmentioning
confidence: 99%